Effect of Ascaridia galli infection on histopathologic description, size of small intestines villi surface and body weight change in starters - Zalizar, L; F, Satrija; R, Tiuria; Astuti, D.A (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Nematode Ascaridia galli is an important parasitic disease in poultry and is responsible for considerable economic losses in retarded growth and lowered egg production. The effects of A. galli infection based on histopathologic description, size of small intestines villi surface and body weight change in starters was investigated. One hundred and thirty five day old chicks (DOC) were divided into three groups for three levels of infection dose rate (0,800 and 8000 infective eggs) with 3 replications of 45 DOC each. Infections were carried out every week respectively from week 2th until week 5th. Results showed that the infection of A. galli caused degeneration and necroses in villi ephitelial cells and crypts of small intestine and infiltration of leucocytes. In the heavy infection group some epithelial cells were replaced by fibrocytes. A. Â galli infection decreased daily body weight gain of starter lower (5.5% in light and 13.4% in heavy dosage infection) compared to that of the non infected group. After six weeks of heavy infection the size of small intestine villi surface was decreasing to 20.0%, while the daily body weight gain was decreasing to 12.3% compared to that of the non infection group. Key words: Ascaridia galli, Starter, Productivity